2016
DOI: 10.5505/tjtes.2016.58712
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Hand Functions Among Children Diagnosed with Autism Spectrum Disorder with Upper Extremity Trauma History

Abstract: BACKGROUND: The present study was designed to compare hand function in autistic children with history of upper extremity trauma with that of autistic children those who do not have history of trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Research shows that children with autism spectrum disorder have a lower somatosensory perception than normotypical age-matched children [5][6][7][8]. Other studies also emphasized that the hand function is less developed compared with children of typical development [9].…”
Section: Introductionmentioning
confidence: 99%
“…Research shows that children with autism spectrum disorder have a lower somatosensory perception than normotypical age-matched children [5][6][7][8]. Other studies also emphasized that the hand function is less developed compared with children of typical development [9].…”
Section: Introductionmentioning
confidence: 99%
“…The authors also found strong positive correlations between sensory processing and motor development in the preterm group. Along these lines, Huri, Şahin, and Kayıhan (2016) reported that autistic children with upper extremity trauma history had poorer somatosensory perception and hand function compared with other autistic children. Huri, Mehr, Altuntaş, and Kayiha (2014) observed that normally developing children choose hard objects more often than soft objects when compared with children with pervasive developmental disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Along these lines, Huri, Şahin, and Kayıhan (2016) reported that autistic children with upper extremity trauma history had poorer somatosensory perception and hand function compared with other autistic children. Huri, Mehr, Altuntaş, and Kayiha (2014) observed that normally developing children choose hard objects more often than soft objects when compared with children with pervasive developmental disorder. Regarding body weight, Handal, Lozoff, Breilh, and Harlow (2007) found that BMI affects PD as overweight children have poorer motor performance compared with normal weight children.…”
Section: Introductionmentioning
confidence: 99%
“…In several populations, the ability to assess manual dexterity using 9-HPT has been demonstrated, such as stroke, chronic nonprogressive childhood encephalopathy, cerebellar impairment, Parkinson's disease and multiple sclerosis (Wang, Bohannon, Kapellusch, Garg, & Gershon, 2015). However, research using 9-HPT in the atypical population, as in ASD, is scarce and did not seek to investigate laterality (Huri, Şahin, & Kayıhan 2016;Lidstone, Miah, Poston, & Beasley, 2020).…”
Section: Introductionmentioning
confidence: 99%